The changing pattern of COVID-19 in Nepal: A Global concern- A Narrative Review - Banerjee, Indrajit; Robinson, Jared; Kashyap, Abhishek; Mohabeer, Poornasha; Shukla, Ananya; Leclézio, Alexandra (Nepal Journal of Epidemiology, 2020)
This narrative review of the literature aims to assess the impact of COVID-19 on the younger age group in terms of the Global mortality of COVID-19 in comparison to Nepal. An extensive literature survey of English literature was conducted using Pubmed, Medline, Google Scholar, Embase, WHO Nepal Situation Updates on COVID-19, Situation update report, Ministry of Health and Population-Nepal from January 25, 2020 to June 20, 2020. According to the Ministry of Health and population of The Government of Nepal, as of June 20, 2020, out of a total of 8,605 laboratory confirmed cases reported to date, the pattern shows that most of the cases fell into the cohort of 21-30 years (37.72%), followed by 11-20 years (24.35 %), 31-40 years (21.97%) and 41-50 years (9.2%). To date Nepal has recorded a total of twenty-two deaths. At first evaluation these figures may not strike one as alarming, but on further investigation it is noted that the mean age is 42. 32 ± 19.632 SD years, and out of which male patients accounted for 77.3% and female accounted for 22.7%. The current situation of COVID-19 and how it develops in Nepal should be closely monitored and could be of international concern as it may be the early indicator of a changing pattern in COVID-19 infections. Nepal may therefore act as a global watch dog, due to the fact that the world could very possibly expose the younger age group under the notion that they are more resilient to the virus, when in reality that notion may be changing. This trend must be monitored and further investigated in order to establish the risk of the events unfolding in Nepal.